SITUS MAKAM KUNA ISLAM JERA’ LOMPOE DAN STRATIFIKASI SOSIAL DI SOPPENG - nfn Muhaeminah (WalennaE, 2001)
Soppeng is one of the kingdoms that related with Suppaq, Luwu, Bone, Tanete, and Wajo kingdoms. The relationship was proved by the existence of Soppeng outsiders tombs, on ancient Islamic tombs of Jera' Lompoe. It was acknowledge from tombs size, types or its gravestone that they came from "the upper" class, or anakarung, Topanrita, Tosugi. There were four size and types which discovered around Islamic cemetery Jera' Lompoe: stone tombs with monolith gravestone; tomb with dome and pile orders technique and menhir type gravestone; pile orders tombs with rectangular gravestone; and large, wide tombs with cylindrical gravestone. Tombs shape and its gravestone types described the strong pre-Istam influence in Islamic periods in Soppeng.